(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: To determine distribution and antibiotic resistance characteristics of Escherichia coli isolated from blood cultures at Military Hospital 103 in 2023. Subjects and Methods: This was a cross-sectional study. The subjects of the study were E. coli strains isolated from blood cultures. Results: There were 141 E. coli strains isolated during the study period. Of which, 65.96% of all strains isolated were in the age group 65 years and older. E. coli strains isolated from men were similar to that from women, and they were most commonly isolated in the Department of Infectious Diseases (44.68%). E. coli strains were highly susceptible to carbapenems (95.74% - 100%), followed by aminoglycosides (72.34% - 98.58%), penicillin combined with beta-lactamase inhibitors (63.04%). E. coli strains had low susceptible rates to cephalosporins (29.20% - 64.18%), fluoroquinolones (38.30%), and trimethoprim/ sulfamethoxazole (27.66%). The rate of ESBL (Extended Spectrum Beta-Lactamases) producing E. coli strains is very high (68.46%). The rate of resistance to antibiotics for ESBL-producing E. coli is higher than that of non-ESBL-producing E. coli. Conclusion: E. coli isolated from blood cultures is most commonly isolated in the group of 65 years old and older, most of them produce ESBL, and are highly sensitive to carbapenem and amyloglycoside antibiotics.